Make an Arabic Language Quiz Using The Kahoot Application - Sirojudin, Ahmad; Ma'arif, Syamsul; Shalihah, Siti; Uyuni, Yuyun Rohmatul (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2024)
The Kahoot application is a game-based learning platform that is used as educational technology in schools and other educational institutions. The platform allows users, including students and teachers, to create and take interactive learning quizzes called